SOSIALISASI DAN ENKULTURASI TRADISI PENGANUT MADRAISME DALAM KELUARGA DI KAMPUNG CIREUNDEU KOTA CIMAHI - Yani Achdiani (Indonesian Journal of Dialectics, 2012)
Up to the present time, we still find people who profess the ism which is no longer suitable for the modern or religious society. This research is a case study which is purposed to understand the existence of Madraism followers, which is known as “SundaWiwitan”, at Cireundeu village, Cimahi city. The problem is, why Madraism is still faithfully professed, meanwhile another ismsuch as Ahmadiyah has been prohibited. The method used in the research is descriptive analytical method and field data aredescribed using qualitative approach (phenomenal paradigm). Data collecting was conducted through observation and deepinterview. Validity of the data is measured using triangulation technique through confirmation and check and recheck betweenthe results of observation and deep interview. The objective of the research is to analyze socialization and enculturation ofMadraism follower tradition within the family life at Cireundeu village using Structural-functional Talcot Parson System theory.The results of the research are as follows: (1) socialization and enculturation process of Madraism have implanted since thechildhood with the aim at having ability to live in global era without losing their identity, (2) the process occur in harmonious, charismatic, and noble life with the content of social ethic, norms, Sundanese custom, and Madraism, (3) the family is a major factor in developing personalized value, (4) the process pattern in accordance with the intercourse between parents and children based on influence of parents through stages of imitation, suggestion, identification, and sympathy. Theoretical implication of the study indicates that the findings of this study support the Structural-functional theory and Social System. Socialization in a unit of family describes a network of relatives (kin-group) which is continued cooperatively based on values, norms, and social customs. Based on the suggestion of the research, the concept proposed is a comprehensive socialization and enculturation by involving all elements to strengthen the local tradition.